PENGARUH JUMLAH UANG SAKU DAN KONTROL DIRI TERHADAP POLA KONSUMSI MAHASISWA JURUSAN EKONOMI PEMBANGUNAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG - Ulfa Lutfiah; Yohanes Hadi S. (Jurnal Pendidikan Ekonomi, 2015)
The purpose of this study was to determine (1) whether or not the influence of the amount of the allowance to the pattern of consumption of students from the Department of Economic Development, Faculty of Economics, (2) whether or not the influence of self-control on the consumption patterns of students from the Department of Economic Development, Faculty of Economics, (3) there is or whether the effect of the amount of pocket money and self-control of the consumption patterns of students from the Department of Economic Development Faculty of Economics, University of Malang. The data taken is primary data obtained through a questionnaire which was distributed by the researchers to students who then analyzed using SPSS 16 for windows. Results of the study are: (1) the effect of which is directly proportional to the amount of the allowance towards the consumption patterns of students, if the amount of pocket money students high and good management, the consumption patterns of students will be rational, but if the amount of the allowance is high and management is low, the pattern of consumption is not rational (2) high self-control, the impact on both the consumption patterns of rational consumption patterns, (3) The amount of pocket money and self-control simultaneously affect consumption patterns.